PENGARUH PENGELUARAN PEMERINTAH TERHADAP PDRB SEKTOR PERTANIAN DI PROVINSI SULAWESI UTARA - Christi S. Manoi; Grace A.J. Rumagit; Joachim N.K. Dumais; Rine Kaunang (Universitas Sam Ratulangi, 2015)
ABSRACTThe objective of this research is to identify the effect ofgovernment expenditure to GRDP of agriculture sector in North Sulawesi Province. This research was conducted from October to November 2014 by using secondary data in form of tim series data in 2005-2013 period obtained from North Sulawesi Central Bureau of Statistics and North Sulawesi Province Agriculture and Livestock Department. Analysis of data uses simple linear regression method using Minitab Statistics program version 16.Research result showed that 80,3 percent of GRDP Agriculture sector was significantly affected by Government expenditureat 30 percent significance level, therefore it can be concluded that the increasing of government expenditure of agriculture sectorincrease GRDP of agriculture sector in North Sulawesi Province.